Efektifitas Penggunaan Alat Peraga Sederhana untuk Meningkatkan Aktivitas Belajar Siswa - Baiq Yuni Wahyuningsih (ISLAMIKA, 2020)
This research was conducted to see how effective the use of media / teaching aids to improve student learning activities and outcomes in mathematics learning, especially in the ability to count addition and reduction of fractions. Learning activity intended here is how students can involve all aspects of psychophysics, both physical and spiritual so that accelerated changes in behavior can occur quickly, precisely, easily and correctly, both related to cognitive, affective and psychomotor aspects. This type of research is a classroom action research (CAR) which is part of an action research conducted by a teacher in class while teaching. This research uses a qualitative and quantitative approach. A qualitative approach was used to process data from observations of student and teacher activities. While the quantitative approach is used to process the test result data to determine student learning outcomes. This research was conducted in 2 (two) cycles. Each cycle consists of 3 times face to face. In general, each cycle starts from the action planning, the implementation stage of the action / implementation, observation and evaluation to the reflection stage. Based on the results of research and data analysis that has been done, it can be concluded that the use of teaching aids can increase student learning activities with a percentage in the first cycle of 1.34% and the second cycle of 3.33%. Thus student learning activities in general have increased / increased by a percentage of 1.99%. From the Fair category in Cycle I it becomes the Very High category after cycle II.